2018
DOI: 10.1515/geo-2018-0063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aquifer hydraulic characteristics using geoelectrical sounding, pumping and laboratory tests: A case study of Lokoja and Patti Formations, Southern Bida Basin, Nigeria

Abstract: The hydraulic characteristics of aquifers in Lokoja and Patti Formations were investigated using combination of vertical electrical sounding (VES), pumping and laboratory tests. A total of 20 VES (10 each in areas underlain by Lokoja and Patti Formations) were carried out at different locations with 5 pumping tests around VES stations in order to determine the geoelectric layers, thickness, depths to water table and groundwater potential of the area. 21 samples extracted fromaquiferous units of surface outcrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Thus, the potential recharge is expected to be regional, and, in most cases, such recharges are likely to favor deep aquifers [25]. However, this is contrary to the study by [24], which indicated that groundwater in some specific areas is controlled by weathered zones [26].…”
Section: Geology and Hydrogeologymentioning
confidence: 83%
See 1 more Smart Citation
“…Thus, the potential recharge is expected to be regional, and, in most cases, such recharges are likely to favor deep aquifers [25]. However, this is contrary to the study by [24], which indicated that groundwater in some specific areas is controlled by weathered zones [26].…”
Section: Geology and Hydrogeologymentioning
confidence: 83%
“…Both step and constant pumping tests were implemented in all boreholes without an observation well. Specifically, the step test aims at determining the discharge that is within the well aquifers' yield limits, which can be tested by a continuous constant pumping test [18,19,26]. All boreholes had a diameter of 6 inches and depths ranging between 25 and 150 m. Thus, a submersible pump with a capacity of 5.5 HP was used.…”
Section: Execution Of Pumping Testsmentioning
confidence: 99%
“…The sand occurs at depths range of 2-7.9 m. Although sand is a good aquiferous unit for groundwater, the depths of occurrence and the thicknesses of the sand unit is low. The thickness of the sand and the thickness/nature of the overlying unit are important factors to be considered in groundwater abstraction [18].…”
Section: Figure 5 Geoelectric Section Along the Profile In The Basement Complex Terrainmentioning
confidence: 99%
“…to estimate soil hydraulic conductivity, both from laboratory analysis, indirect methods such as grain size analysis and from hydraulic tests. Besides the grain size, other factors that could affect hydraulic conductivity include degree of compaction, porosity and shape of the grains (Ige et al, 2018). Changes in groundwater table are dependent on the hydraulic conductivity, empirical estimation of the hydraulic properties of aquifer to establish its viability becomes necessary.…”
Section: Introductionmentioning
confidence: 99%